Questioning the role of questions: new primary teachers' realisations of over-reliance on questions in scientific dialogue. Issue 2 (3rd April 2019) - Forster, Colin; Penny, Jude; Shalofsky, Russ
ABSTRACT: This article reports on research undertaken with final year undergraduate student teachers, in which they examined their deployment of questions to promote children's observation and curiosity in primary science. The study adopted elements of action research methodology to enable student teachers to engage deeply with evidence-based evaluation of their practice. Specific aims of the study were for student teachers to extend their understanding of quality questioning in primary science and its impact on children's intellectual engagement, examine the detail of their practice of questioning through a supported action research process, and develop their understanding of data analysis for improving practice. Student teachers taught lessons, on the topic of plant growth, to small groups of Year 2 children and evaluated their questioning strategies immediately afterwards and analysed transcript data of their interactions. They identified specific ways in which their practice of questioning could be improved and put these into practice in a follow-up lesson with the same children. Student teachers were astonished to discover how over-reliant they were on questions as their default strategy for engaging children in science-related dialogue. The process of analysing transcripts was deemed to be insightful in helping them to identify ways to develop their practice and to define key characteristics of effective questioning in primary science and to appreciate the power of self-evaluation to enhance the quality of teaching and learning.